Residual clip after laparoscopic radical prostatectomy surgery and radiotherapy. A case report - Ismael Leblanch Hernández (Medisur)
Laparoscopic and robotic radical prostatectomy are two treatment options for prostate cancer. These procedures, although advanced, are not without risks. Some of the rare complications, but with enough cases reported in the literature, are the migrations of the hemostatic clips used in surgery. A case of a 56-years-old patient, who underwent nerve-sparing laparoscopic radical prostatectomy, who suffered from lower obstructive symptoms as a result of a bladder foreign body plus irritative vesicourethral symptoms, as a result of radiotherapy was presented. The patient had a calcified plastic clip removed 45 days after radiotherapy, three years after surgery (five clips had been removed a year earlier). Due to the unusual and delicate nature of the case and as a warning about the precaution that should be taken when combining a bladder foreign body with radiotherapy and when using these devices during the surgical act, this presentation was presented.